2004
DOI: 10.1074/jbc.m402325200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the NH2-terminal WD/EPF Motif in the Phosphorylation-activated Protective Function of Mammalian Hsp27

Abstract: Hsp27 is expressed at high levels after mild heat shock and contributes to making cells extremely resistant to subsequent treatments. The activity of the protein is regulated at the transcriptional level, but also by phosphorylation, which occurs rapidly during stress and is responsible for causing the dissociation of large 700-kDa Hsp27 oligomers into dimers. We investigated the mechanism by which phosphorylation and oligomerization modulate the protective activity of Chinese hamster Hsp27. In contrast to oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 53 publications
7
111
1
Order By: Relevance
“…Contrary to expectations, the higher s 20,w peak is broader than the lower s 20,w value peak, making it likely that there is a distribution of large oligomers of different sizes and/or shapes. This polydispersity is consistent with cryo-electron microscopy (17) and gel filtration studies (12)(13)(14)(15)(16).…”
Section: Phosphorylated Hsp27 Size and Molecular Chaperone Functionsupporting
confidence: 71%
See 1 more Smart Citation
“…Contrary to expectations, the higher s 20,w peak is broader than the lower s 20,w value peak, making it likely that there is a distribution of large oligomers of different sizes and/or shapes. This polydispersity is consistent with cryo-electron microscopy (17) and gel filtration studies (12)(13)(14)(15)(16).…”
Section: Phosphorylated Hsp27 Size and Molecular Chaperone Functionsupporting
confidence: 71%
“…Some in vitro studies concluded that the unphosphorylated oligomeric Hsp27 (or the murine isoform Hsp25) protects proteins against aggregation better than does the phosphorylation mimic (13,19,27), whereas others found no difference (16,28,29), and still other studies found that the mimic protects better than does the unphosphorylated wild type (27,30,31). In-cell studies found that phosphorylation of Hsp27 was essential for thermo-protection of actin filaments (32), and the Hsp27 phosphorylation mimic decreased inclusion body formation better than did unphosphorylated Hsp27 (33).…”
mentioning
confidence: 99%
“…Phosphorylation reduces the average oligomer size, and increases oligomeric polydispersity and rate of subunit exchange of αBc [98,[132][133][134], whereas it leads to a dramatic decrease in the size of Hsp27 oligomers, such that the triply phosphorylated isoform is predominately dimeric in solution [135,136]. Thus, under stress conditions, Hsp27 is phosphorylated, triggering dissociation of the high molecular mass Hsp27 oligomers [117,135,137,138] and an increase in the amount of exposed hydrophobicity on the newly formed Hsp27 dimers [139]. Phosphorylation also affects the cellular distribution of some sHsps.…”
Section: Phosphorylationmentioning
confidence: 99%
“…However, even in the young lens, αB-crystallin is extensively phosphorylated [113,118]. All three sites of serine phosphorylation of Hsp27 are mediated by MAPKAP kinases [119,120]. In the brain, some of the αB-crystallin isolated from the proteinaceous aggregates of patients with degenerative diseases [121], amyloid plaques and Lewy bodies is phosphorylated [68].…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%